The Victory Banner over the Reichstag film, document, and ritual in Russia's contested memory of World War II - Hicks, Jeremy ca. 20./21. Jahrhundert (University of Pittsburgh Press, 2020)
"In one of the most iconic images from World War II, a Russian soldier raises a red flag atop the ruins of the German Reichstag on April 30, 1945. Known as the Victory Banner, this piece of fabric has come to symbolize Russian triumph, glory, and patriotism. Facsimiles are used in public celebrations all over the country, and an exact replica is the centerpiece in the annual Victory Parade in Moscow's Red Square. The Victory Banner Over the Reichstag examines how and why this symbol was created, the changing media of its expression, and the contested evolution of its message. From association with Stalinism and communism to its acquisition of Russian nationalist meaning, Jeremy Hicks demonstrates how this symbol was used to construct a collective Russian memory of the war. He traces how the Soviets, and then Vladimir Putin, have used this image and the banner itself to build a remarkably powerful mythology of Russian greatness"--
Keywords: Geschichte 1945-; Geschichtspolitik; Kollektives Gedächtnis; Schlacht um Berlin -- Motiv; Russlandfeldzug -- 1941-1945, Motiv; Russland; Sowjetunion; Berlin, Battle of, Berlin, Germany, 1945 / Motion pictures and the war; World War, 1939-1945 / Soviet Union / Flags; Soviet Union / Raboche-Krestʹi͡anskai͡a Krasnai͡a Armii͡a / Flags; Flags / Soviet Union; Emblems, State / Soviet Union; Collective memory / Russia / History / 20th century; National characteristics, Russian; War and society / History / 20th century; Soviet Union / Raboche-Krestʹi͡anskai͡a Krasnai͡a Armii͡a; Armed Forces / Flags; Collective memory; Emblems, State; Flags; War and motion pictures; War and society; Germany / Berlin; Russia; Soviet Union; 1900-1999; History